Towards experiential representation in architecture - Fuente Suárez, Luis Alfonso de la (Journal of Architecture and Urbanism, 2016)
Planning and predicting the experiences that buildings will produce is an essential part of architectural design. The importance of representation lies in its ability to communicate experiences before a building is materialized. This article will treat the topic of representation of architecture works without putting aside our direct experience with edifices. By understanding the perceptual, associative and interactive phenomena that arise from the human encounter with buildings, it becomes possible to comprehend the representation of these phenomena through pictorial means. The first objective of this theoretical article is to define the inherent and unavoidable factors that are present in the creation and interpretation of all architectural representations, regardless of the technical means used. Any representation conveys two processes: the representation of experience (a creative process), and the experience of representation (an interpretive process). Furthermore, there exist two layers in any representation: the what (the architectural object) and the how (the representational medium). The second objective is to suggest alternatives to visual realism, in order to create representations that embody the particular phenomena that an architectural work will be able to produce. On the one hand, representations that pretend to copy reality produce in the observers detailed visual experiences; on the other hand, certain representations reflect the experiences themselves after they have been produced; they represent buildings as they are transformed by experience. This article focuses on those representations that are not only the reflection of an object, but also the reflection of our way of experiencing it.